Correlation Between Beat‐to‐Beat QT Interval Variability and Impaired Left Ventricular Function in Patients with Previous Myocardial Infarction - Hiromoto, Kenji (Ann Noninvasive Electrocardiol, 2006)
Background: Beat‐to‐beat QT interval variability (QTV) is associated with sudden cardiac death and New York Heat Association functional class severity. We sought to evaluate the relationship between QTV and left ventricular (LV) function in patients with previous myocardial infarction (MI). Methods: Fifty‐nine patients with previous anterior MI were enrolled. LV ejection fraction (EF), LV end‐systolic volume index (LVESVI), and LV end‐diastolic volume index (LVEDVI) were measured by LV contrast angiography. QT interval was measured by automated analysis of 512‐beat records of 12‐lead electrocardiogram. The mean interval, standard deviation and variance in RR and QT intervals, and the QT variability index (QTVI) were calculated for each patient using two leads that corresponded with and without the infarction site. High‐frequency power, low‐frequency power, total‐frequency power, and the ratio of low‐frequency to high‐frequency power in RR and QT intervals were calculated. Results: While measured indices of RR intervals and indices of QT intervals, which did not correspond with the infarction site, did not correlate with differences in LV function, measured indices of QT intervals, which corresponded with the infarction site, did correlate with differences in LV function. However, there were no correlations between the ratio of low‐frequency to high‐frequency power in QT intervals and EF or LVEDVI. Correlations between QTVI and LV function were observed, particularly between QTVI and LVESVI (r = 0.712, P < 0.0001). Conclusion: In patients with previous anterior MI, there was variability in temporal dispersion of QT interval and a strong correlation between QTV corresponded with the infarcted site and LV function.